B-type natriuretic peptide levels and diagnostic accuracy: excess fluid volume - Melina Maria Trojahn; Sofia Louise Santin Barilli; Daniela de Souza Bernardes; Letícia Lopez Pedraza; Graziella Badin Aliti; Eneida Rejane Rabelo-Silva (Universidade Federal do Rio Grande do Sul, 2020)
ABSTRACT Aim: To analyze the behavior of B-type natriuretic peptide (BNP) in the presence of defining characteristics (DCs) of the nursing diagnosis Excess fluid volume (00026) in patients hospitalized for acute decompensated heart failure. Methods: Cohort study of patients admitted with acute decompensated heart failure (September 2015 to September 2016) defined by Boston Criteria. Patients hospitalized for up to 36 h with BNP values ≥ 100 pg/ml were included; BNP values at baseline-final assessment were compared by Wilcoxon test, the number of DCs at baseline-final assessment was compared by paired t-test. Results: Sixty-four patients were included; there was a significant positive correlation between delta of BNP and the number of DCs present at initial clinical assessment. Conclusions: The behavior of BNP was correlated to the DCs indicating congestion. With clinical compensation, DCs and BNP decreased. The use of this biomarker may provide additional precision to the nursing assessment.